THE RELATIONSHIP BETWEEN EDUCATION AND HEALTH - Muhlisa Qahramonova; Gulzoda Xaliqulova (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Education is integral to social and financial improvement and has a profound impact on population health. We overview evidence for the health advantages related to schooling in the context of a socioecological model of health. The health advantages of schooling accrue at the individual level (e.g., skill improvement and access to resources); at the community level (e.g., the health-related characteristics of the environments in which humans live); and in a large social and cultural context (e.g., social policies, residential segregation, and unequal access to educational resources). All of these upstream elements may additionally make contributions to health outcomes, while factors such as ability to navigate the fitness care system, educational disparities in non-public health behaviors, and publicity to continual stress act as more proximate factors. After exploring the literature linking health and education, we describe a project to engage residents of a low-income city community in a method of growing causal models to attempt to identify new links between education and health and help refine our understanding of the complicated phenomena that form this relationship.